Increasing Students’ Proficiency to Develop Ideas and Build Coherence in Writing Descriptive Text by Applying Quartet Game - Indah Puspitasari; Agung Budi Kurniawan (Jurnal Humaniora, 2017)
We are a research team who explore the application of quartet card game to enhance students’ proficiency in mastering descriptive text. We conducted the research through a classroom action research frame work. We got students of Class X of SMK Pringkuku Pacitan in the academic year 2016-2017 as our research subject. In our research, we explore the effect of quartet card game to increase students’ writing proficiency and motivation in writing descriptive text. Overall, we got the fact that quartet card game could increase both of them In this article, we present two aspect of the students’ writing proficiency. First, it is the ability to develop ideas. Second, it is the ability to build coherence. We got the data from: students writing score. In the students’ ability to develop ideas in writing descriptive text, we got the fact that the application of quartet game could give effect to students as follow: 1).Students could get creative idea, 2).Students could develop idea in every paragraph, 3).The situational idea based on descriptive text character is easy to be got by students, 4).Students could limit their ideas into descriptive text demand, so it does not exist the case of out of context ideas, 5).The content is informative to present descriptive text, 6).The quality of descriptive text is very interesting for readers. In the students’ ability to build coherence in writing descriptive text, we got the fact that the application of quartet game gives effect as follow: 1).The ideas were presented in a well coherence story, 2).The use of cohesion technique to correlate ideas to one another, 3).The arrangement seems to be prepared very well, 4).The organizations of story make readers to be able to understand the text story easily, 4).The structure of texts follows the generic structure of descriptive text or genre.